1993
DOI: 10.1073/pnas.90.11.5071
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the mouse protamine 1 promoter in transgenic mice.

Abstract: Protamines are small arginine-rich proteins that package DNA in spermatozoa. The mouse protamine 1 (Prm-1) gene is transcribed exclusively in post-meiotic spermatids. To identify elements in the Prim-promoter required for spermatid-specific transcription, we generated transgenic mice by microin'ection of transgenes containing Prm-l 5' flanking sequences with 5' truncations or internal deletions of conserved sequences linked to a marked Prm-1 gene. We also tested Prm-l promoter regions with a heterologous human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
2

Year Published

1993
1993
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 34 publications
3
69
0
2
Order By: Relevance
“…For example, restriction patterns and densitometric analyses showed that line 58 contained a single copy of the PrmCre transgene, yet showed virtually the same testis recombination signal as the line containing more than 100 copies (78). This variability is similar to results obtained with other Prm1 promoter-driven transgenes (13,30).…”
Section: Prmcre Transgenes Efficiently Recombine Target Allelessupporting
confidence: 75%
“…For example, restriction patterns and densitometric analyses showed that line 58 contained a single copy of the PrmCre transgene, yet showed virtually the same testis recombination signal as the line containing more than 100 copies (78). This variability is similar to results obtained with other Prm1 promoter-driven transgenes (13,30).…”
Section: Prmcre Transgenes Efficiently Recombine Target Allelessupporting
confidence: 75%
“…To ascertain whether the MT flanking regions have enhancer activity, we combined them with an hGH reporter gene with a minimal (83-bp) promoter that responds well to heterologous enhancers, including those from MT-I, elastase I, and protamine I genes (17,21,34). The tissue distribution of hGH expression in five transgenic mice made with the hGH gene alone was compared with that obtained with five mice that carry the hGH gene flanked by the MT sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Testis-specific promoters with cis-acting sequences near the start of transcription have also been observed for genes expressed in spermatocytes in mammals. For example, <200 bp of promoter region are sufficient for expression of the lactate dehydrogenase C and protamine 1 genes in testis extracts or transgenic mouse testes (Zambrowicz et al 1993;Goldberg 1996). These parallels evoke the possibility that testis-specific components of the general transcription machinery may also play an important role in the male germ cell-specific gene expression programs in mammals.…”
Section: The Primary Spermatocyte Transcription Programmentioning
confidence: 99%